Inter-ethnic relations of young people in a divided community - Ajduković, Dean (Array, 2008)
The experiences of post-conflict societies show that the process of trust building between former adversaries and normalization of social life in the community is slow and burdened with multiple obstacles. Our studies of social reconstruction in the city of Vukovar (Croatia) identified factors that hinder this process and the capacity to move forward after massive traumatization and losses the population has suffered. In this previously well integrated multi-ethnic community division along ethnic lines is evident in many aspects of social life, including schooling. The children attend separate classes mostly based on their ethnic background, with the curriculum provided in Croatian or in Serbian language. This strongly limits opportunity for inter-ethnic contact and interaction as the basic condition for normalization of social relations. In the present study we explored the attitudes towards various aspects of schooling among young people, their parents and teachers in a representative sample (N=1784) from two ethnic groups. These attitudes were related with measures of inter-ethnic relations: out-group contacts, friendships, and tendency to discriminate against the out-group. Young people had more out-group biases, negative attitudes, and chose discriminative behaviors towards peers from the other ethnic group more often than the adults. The results are discussed in the view of social consequences that growing up in a divided community has for young people, complexity of minority education issues from the rights perspective, implications of continued separate or integrated schooling, and the ways to encourage cooperation between groups in this divided community.